The Association between Bilateral Deficit and Athletic Performance: A Brief Review - Petra Železnik; Vita Slak; Žiga Kozinc; Nejc Šarabon (MDPI AG, 2022)
An abundance of information can be found in the scientific literature regarding the bilateral deficit (BLD) in different contraction types, including its possible underlying mechanisms. On the other hand, studies on the relationship between BLD and athletic performance have only begun to emerge in recent years. The purpose of this review article is to assemble and analyze the literature on the topic of the relationship between BLD and athletic performance. After a detailed review of the scientific databases, we analyzed 10 relevant scientific articles. BLD calculated from outcomes of vertical jumps was positively related to the ability to change direction quickly in volleyball, basketball, tennis and student population, but not in soccer. Sprint running performance does not seem to be associated with BLD, while one study suggested that a smaller BLD is associated with a more efficient start in a sprint. Apart from the associations with change in direction performance, there is little evidence to support the association between BLD and athletic performance; thus, further research is required in other sports, incorporating sport-specific performance outcomes and multiple tasks to calculate the BLD.